IDENTIFICATION OF POVERTY PREDICTORS IN EX-RESIDENCY OF BANYUMAS IN TERMS OF HUMAN RESOURCES ASPECT - Diah Setyorini Gunawan; Abdul Aziz Ahmad; Ratna Setyawati Gunawan (Jurnal Ekonomi dan Manajemen, 2022)
This study aimed to identify the predictors to determine whether the regencies are in the category of high or low poverty rate in ex-Residency of Banyumas. The predictors used in this study represented aspects of human resources. The predictors included population growth, education level, and health level. The analytical method used in this study was discriminant analysis. Discriminant analysis was used to identify predictors of poverty in ex-Residency of Banyumas. This study classified four areas in the research areas where Banyumas Regency, Cilacap Regency, and Banjarnegara Regency were included in the classification of the regency group with low poverty rates, while Purbalingga Regency was included in the regency group with high poverty rate. Furthermore, the determinant analysis obtained the results that population growth and health level were the predictors to determine whether the regencies are in the category of high or low poverty rate in ex-Residency of Banyumas. In addition, population growth was the best predictor of poverty in terms of human resources. Based on the research findings, the implications of this research are 1) the central government and local governments in the areas of ​​Ex-Residency of Banyumas should always seek to suppress population growth rate through the Family Planning Program (KB), 2) the central government and local governments in the areas of ​​Ex-Residency of Banyumas should also continuously strive to increase the number and quality of health facilities available to the community.